Amino-acid and biochemical composition of whole body and molt of the Indian white shrimp - Dayal, J Syama; Ali, S Ahamad; Sarada, C (Indian Journal of Fisheries, 2011)
The amino acid and biochemical composition of molt (exuvia) and whole bodyof the shrimp, Fenneropenaeus indicus were analysed along with morphometricrelations. The wet weight of exuvia (0.22 Â± 0.07 g) is nearly 4.8% of the wholeshrimp weight (4.50 Â± 1.42 g). The goodness fit statistics R2 revealed highlysignificant relationship in weights of wet exuvia- wet shrimp, dry exuvia- wetshrimp and dry exuvia- dry shrimp with values 0.90, 0.89 and 0.88, respectivelyindicating that more than 88% of variation of the data explained by themodels. The crude protein and crude fat contents of whole shrimp expressedon dry matter basis were 3-5 times higher than those found in exuvia. However,the exuvia of the shrimp had more than twice the dry matter and aboutfour times ash contents when compared to that of whole shrimp body. Theamino-acid composition of the whole shrimp body and the exuvia expressed ondry matter basis were 63.37 and 11.94 per cent, respectively. Glutamic acid,leucine and aspartic acids in the whole shrimp and glutamic acid, glycine andalanine in the exuvia were the predominant amino acids.